(NmATEMATI^ESKAQ KIBERNETIKA I EE PRILOVENIQ K BIOLOGII (B:s [(NsBORNIK STATEJ(B] /s - (NkRU[INSKIJ(B, (NlEONID wIKTOROWI^s; (NmOSKOWSKIJ GOSUDARSTWENNYJ UNIWERSITET IM(B. (Nm(B.(Nw(B. (NlOMONOSOWA(B.s (NmEHANIKO(B-(NMATEMATI^ESKIJ FAKULXTETs ((NmOSKWA (B:s (NiZD(B-(NWO mOSK(B. (NUN(B-(NTA(B,s, 1987)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NkIBERNETIKA (B- (NpRIMENENIE W BIOLOGII (B- (NsBORNIKIs